2012
DOI: 10.1007/s00726-012-1384-x
|View full text |Cite
|
Sign up to set email alerts
|

d-Amino acids in the brain and mutant rodents lacking d-amino-acid oxidase activity

Abstract: D-Amino acids are stereoisomers of L-amino acids. They are often called unnatural amino acids, but several D-amino acids have been found in mammalian brains. Among them, D-serine is abundant in the forebrain and functions as a co-agonist of NMDA receptors to enhance neurotransmission. D-Amino-acid oxidase (DAO), which degrades neutral and basic D-amino acids, is mainly present in the hindbrain. DAO catabolizes D-serine and, therefore, modulates neurotransmission. In the brains of mutant mice and rats lacking D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 112 publications
1
37
0
Order By: Relevance
“…A role for DAO in the VTA cannot be assumed just by virtue of its expression therein, since DAO mRNA and immunoreactivity are also detected in frontal cortex (Moreno et al, 1999; Hashimoto et al, 2007; Verrall et al, 2007), yet there is limited evidence for functionality of cortical DAO, and cortical D-serine concentrations are not elevated in the ddY/DAO − mouse (Yamanaka et al, 2012). Our in vivo microdialysis data suggest that VTA DAO is indeed functional (complementing the observations of Fernandez-Espejo et al, 2008), since local injection of the DAO inhibitor sodium benzoate increased extracellular dopamine and its metabolites in medial frontal cortex (Figures 3A–C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for DAO in the VTA cannot be assumed just by virtue of its expression therein, since DAO mRNA and immunoreactivity are also detected in frontal cortex (Moreno et al, 1999; Hashimoto et al, 2007; Verrall et al, 2007), yet there is limited evidence for functionality of cortical DAO, and cortical D-serine concentrations are not elevated in the ddY/DAO − mouse (Yamanaka et al, 2012). Our in vivo microdialysis data suggest that VTA DAO is indeed functional (complementing the observations of Fernandez-Espejo et al, 2008), since local injection of the DAO inhibitor sodium benzoate increased extracellular dopamine and its metabolites in medial frontal cortex (Figures 3A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps DAO inhibition affects a substrate other than D-serine, for example D-alanine, which is a high affinity NMDA receptor co-agonist (Tanii et al, 1994) metabolized by DAO (Molla et al, 2006; Horio et al, 2009), and whose levels rise markedly in rodents lacking DAO (Yamanaka et al, 2012). Alternatively, the injected D-serine may be rapidly removed from the synapse via a transporter (Helboe et al, 2003; Rutter et al, 2007; Burnet et al, 2008b; Sikka et al, 2010), or metabolized by serine racemase (Foltyn et al, 2005; Strisovsky et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SR might regulate the physiological level of D-serine by racemization activity to synthesize D-serine and by α , β -elimination activity to degrade D-serine. DAO is the flavoprotein that converts D-serine to produce the corresponding alpha keto acid, hydrogen peroxide, and ammonia [11]. …”
Section: D-serinementioning
confidence: 99%
“…D-Amino acids are enantiomers of L-amino acids and have been considered to be absent and unnatural amino acids in mammals for a long time. However, the recent development of sensitive analytical methods elucidated the presence of D-amino acids, such as D-serine, D-aspartate, and D-alanine, in mammals [911]. Moreover, studies on the enzymes that synthesize or metabolize D-amino acids have also clarified the localization and functions of D-amino acids in the nervous and endocrine systems and found that D-amino acid synthesis and metabolism are physiologically regulated [1215].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current ecological system on Earth, L-amino acids are predominantly observed in the organisms. On the other hand, the presence of D-amino acids is normally in very trace amounts [5,6], and the origin of this "homochirality" is still unclear.…”
Section: Introductionmentioning
confidence: 99%